2019
DOI: 10.1049/iet-epa.2019.0241
|View full text |Cite
|
Sign up to set email alerts
|

Design of linear voice coil motor with semi‐closed structure

Abstract: A Halbach permanent magnet (PM) tubular linear voice coil motor (LVCM) with a semi-closed structure is developed to enhance the thrust density in this study. Generally, the end of conventional LVCM is open and suffers from the considerable end reluctance. The usage of Halbach array in LVCM makes this problem more prominent although it improves the air-gap flux density greatly. The flux at the end of LVCM can be guided to improve the air-gap flux density. Therefore, this study aims to constrain and direct the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In order to obtain the self-inductance change model of the macro-motion coil (Manh and Chen, 2020;Luo et al, 2019), the equivalent circuit of the macro-motion coil is established, as shown in Fig. 11.…”
Section: Kinetic Model Of Macro-motion Partmentioning
confidence: 99%
“…In order to obtain the self-inductance change model of the macro-motion coil (Manh and Chen, 2020;Luo et al, 2019), the equivalent circuit of the macro-motion coil is established, as shown in Fig. 11.…”
Section: Kinetic Model Of Macro-motion Partmentioning
confidence: 99%
“…The Halbach array consists of two radially magnetised PMs which are in the opposite direction of magnetisation and three axially magnetised PMs. Luo and Lin [15] show the LVCM with Halbach array is a superior topology for its high air‐gap flux density. The Halbach permanent magnet array is mounted on a ferromagnetic support shaft, and the whole part works as a mover.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Scholars have further improved the performance of micro linear motors by using highly magnetic materials, designing Halbach arrays instead of conventional pole structures, as well as applying superconducting materials to make windings [6][7][8]. The electromagnetic linear actuators, as an important development direction of linear motors, have become a research hotspot for high-performance linear servo control due to the advantages of cogging-free torque, high linearity, simple structure, and convenient control compared to conventional permanent magnet synchronous linear motors [9,10].…”
Section: Introductionmentioning
confidence: 99%